The Influence of Storytelling Methods on Early Childhood Character Knowledge in the Dimension of Belief - Tsani, Rahimah; Afdal, Rizki (International Journal of Pedagogy, 2025)
The problem in this study is the low character knowledge of children aged 5-6 years in Tadika Institution. This study aims to determine the effect of storytelling methods on the character knowledge of children aged 5-6 years in the dimension of divinity in Tadika Institution. This study uses a quantitative research type with an experimental method. The sampling technique uses purposive sampling with a sample size of 42 children in Tadika Institution. The data collection technique uses observation techniques with non-test instruments in the form of checklists . The hypothesis test analysis technique uses the paired sample T test on SPSS. Based on the results of the study, it shows a positive influence with a significant value of 0.843. So it can be concluded that the storytelling method has a positive effect on the character knowledge of children aged 5-6 years in the dimension of divinity in Tadika Institution.